Clinical characteristics of hepatitis flares during pregnancy and postpartum in Chinese chronic hepatitis B virus carriers—a prospective cohort study of 417 cases - Wang, Xiaoxiao; Song, Aixin; Lin, Xiao; Lu, Junfeng; Zheng, Sujun; Ma, Lina; Ren, Shan; Zheng, Yanhong; Chen, Xinyue (Frontiers in Immunology, 2022)
Background: In China, it is common for pregnant women with a high load of hepatitis B virus (HBV) to take nucleos(t)ide analogue (NA) to prevent maternal-to-child transmission of HBV. However, the impact of NA intervention on virological and biochemical parameters in pregnant and postpartum women and the safety of drug cessation remain unclear. A prospective observational cohort was established in this study to analyze the clinical characteristics of hepatitis flares in pregnant and postpartum chronic HBV carriers, with or without NA intervention. Methods: Pregnant women who were chronic HBV carriers were enrolled in this study and divided into an NA intervention group and a non-intervention group according to their preferences. Liver function, HBV DNA level, and HBV serological markers were regularly measured during pregnancy and at approximately 6 weeks, 12 weeks, 24 weeks, 36 weeks, and 48 weeks postpartum. Results: A total of 417 patients were enrolled, including 303 in the NA intervention group and 114 in the non-intervention group. The incidence rates of postpartum hepatitis flares in both groups were higher than that of during pregnancy (45.7% vs 10.9%, p < 0.001; 41.2% vs 17.7%, p < 0.001). The second trimester was the peak of the incidence of flares during pregnancy and the incidence peak of postpartum flares was about 6 weeks postpartum. A total of 98% (145/148) of postpartum flares occurred within 24 weeks postpartum. After drug cessation, the incidence rate of flares was 34.1% (44/129). Conclusion: In pregnant chronic HBV carriers, a certain proportion of hepatitis flares occurred during pregnancy and postpartum regardless of whether NA intervention was used, and the incidence of postpartum flares(44.6%) was significantly higher than that (12.8%) of during pregnancy. The flare incidence peaked at approximately 6 weeks postpartum, which may be the time period suitable for treatment. Since 98% of postpartum flares occurred within 24 weeks postpartum, the follow-up after drug cessation should be at least 24 weeks postpartum.